Arbitrage Trading Systems for Cryptocurrencies. Design Principles and Server Architecture - Cristian PAUNA (Informatică economică, 2018)
When dot.com has become a quaint idea, when electronic shops have lost the mass attention, while classical and margin trading has become obsolete, something new is coming: cryptocur-rencies. Hundreds of virtual coins have been invented for a single reason: the profit. The high price volatility of these new markets and the fact that the virtual coins price is not regulated by a central bank or a single exchange, gives us opportunities for arbitrage trading. The existence of important price differences makes possible the profit when an automated system buy cheaper and sell more expensive in the same time. This paper will present the general principles under-pinning the implementation of arbitrage trading software for virtual coins market. The very large number of cryptocurrencies and exchanges fundamentally change the server architecture of the trading software. The distributed price data in hundreds of sources and the technical dif-ferences of each of these data providers make all the things difficult to be implemented in a sin-gle application. The low-latency order calculation needed for the fast delivery before a signifi-cant price change, in the presence of thousands of price quotes coming from hundreds of dis-tributed servers makes everything special.